Different Approach Of Video Compression Technique : A Study - Razali, Sazalinsyah; Hashim, Nik Mohd Zarifie; Yahya, Syazrul Zulhazmee; Khairul Azha , A. Aziz; Salleh, Azahari; Mohamad, Najmiah Radiah (IJSEA, 2014)
-